The Effect of Intellectual Capital to Profitability of Banking Sector Companies Listed in Indonesian Stock Exchange in 2007-2011 - Martha Kartika (Business Accounting Review, 2013)
This study aimed to analyze that influence of intellectual capital on profitability. This study used several control variables that identified as factors that influence profitability, such as Value Added Human capital (VAHU), Structural Capital Value Added (STVA), and Value Added Capital employed (VACA). The population used in this study was companies whose businesses are in banking sectors. Sample was drawn by using purposive sampling method thus result 22 companies that will be used as samples for this study.The hypothesis in this study was tested by using multiple linear regression model. Simultaneous signification test (F test) and partial signification test (t test) with α = 5% are used to test hypothesis. The result of F test showed that Value Added Human capital (VAHU), Structural Capital Value Added (STVA), and Value Added Capital employed (VACA) have significant influence on profitability. The result of t tes showed that Value Added Human capital (VAHU) had no significant influence. Structural Capital Value Added (STVA), and Value Added Capital employed (VACA) have postive and significant influence on profitability.Keywords: Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), Value Added Capital employed (VACA), profitability.